METHANOGENIC CALCITE, 13C-DEPLETED BIVALVE SHELLS, AND GAS HYDRATE FROM A MUD VOLCANO OFFSHORE SOUTHERN CALIFORNIA - Hein J.R.; Normark W.R.; McIntyre B.R.; Lorenson T.D.; Ii C.L.P. (My University, 2006)
Methane and hydrogen sulfide vent from a cold seep above a shallowly buried methane hydrate in a mud volcano located 24 km offshore southern California in· 800 m of water. Bivalves, authigenic calcite, and methane hydrate were recovered in a 2.1 m piston core. Aragonite shells of two bivalve species are unusually depleted in 13C (to -91‰ δ13C), the most 13C-depleted shells of marine macrofauna yet discovered. Carbon isotopes for both living and dead specimens indicate that they used, in part, carbon derived from anaerobically oxidized methane to construct their shells. The δ13C values are highly variable, but most are within the range -12‰ to -91‰. This variability may be diagnostic for identifying cold-seep-hydrate systems in the geologic record. Authigenic calcite is abundant in the cores down to ~1.5 m subbottom, the top of the methane hydrate. The calcite is depleted in 13C (δ13C = -46‰ to -58‰), indicating that carbon produced by anaerobically oxidized methane is the main source of the calcite. Methane sources include a geologic hydrocarbon reservoir from Miocene source rocks, and biogenic and thermogenic degradation of organic matter in basin sediments. Oxygen isotopes indicate that most calcite formed out of isotopic equilibrium with ambient bottom water, under the influence of gas hydrate dissociation and strong methane flux. High metal content in the mud volcano sediment indicates leaching of basement rocks by fluid circulating along an underlying fault, which also allows for a high flux of fossil methane. © 2006 Geological Society of America.
Keywords: 13C-DEPLETED BIVALVE SHELLS; CALIFORNIA MARGIN BASIN; COLD SEEP; METHANE HYDRATE; MUD VOLCANO; Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен